One‐pot Synthesis of CdS Nanocrystals Hybridized with Single‐Layer Transition‐Metal Dichalcogenide Nanosheets for Efficient Photocatalytic Hydrogen Evolution1. (3rd December 2014) - Chen, Junze; Wu, Xue‐Jun; Yin, Lisha; Li, Bing; Hong, Xun; Fan, Zhanxi; Chen, Bo; Xue, Can; Zhang, Hua
Abstract Exploration of low‐cost and earth‐abundant photocatalysts for highly efficient solar photocatalytic water splitting is of great importance. Although transition‐metal dichalcogenides (TMDs) showed outstanding performance as co‐catalysts for the hydrogen evolution reaction (HER), designing TMD‐hybridized photocatalysts with abundant active sites for the HER still remains challenge. Here, a facile one‐pot wet‐chemical method is developed to prepare MS2–CdS (M=W or Mo) nanohybrids. Surprisedly, in the obtained nanohybrids, single‐layer MS2 nanosheets with lateral size of 4–10 nm selectively grow on the Cd‐rich (0001) surface of wurtzite CdS nanocrystals. These MS2–CdS nanohybrids possess a large number of edge sites in the MS2 layers, which are active sites for the HER. The photocatalytic performances of WS2–CdS and MoS2–CdS nanohybrids towards the HER under visible light irradiation (>420 nm) are about 16 and 12 times that of pure CdS, respectively. Importantly, the MS2–CdS nanohybrids showed enhanced stability after a long‐time test (16 h), and 70 % of catalytic activity still remained.